Một vài nhận xét về câu chủ đề trong diễn ngôn chính trị - xã hội trong báo chí tiếng Anh và tiếng Việt (từ góc độ phân tích diễn ngôn) - Nguyễn, Hoà (H. : ĐHQGHN, 2017)
This paper investigates the use of the topic sentence in the popular genre of sociopolitical news discourse acrossEnglish and Vietnamese from a functional and formal perspective. In writing this paper, I hope to bring attention to the differences in the way news discourses are produced and consumed in these two languages. The results of this study clearly point to a number of major differences in terms of order and conceptual content of topics sentences as they occur in English and Vietnamese newspapers. Therefore, writers can improve their writing practices in accordance with international standards as much as readers do their discourse interpretation effectively.